Results of the 20-year period of functioning of the Federal Databank on the natural radiation doses to the population of the Russian Federation - T. A. Kormanovskaya; R. R. Akhmatdinov; G. A. Gorskiy (Радиационная гигиена)
This study is focused on the analysis of the results of the functioning of the Federal Databank on the doses to the public of the Russian Federation from natural and man-made modified radiation background as a part of Joint governmental system of control and accounting of the doses from ionizing exposure in 2001-2020. The mean individual annual effective dose of the public of the Russian Federation from natural sources of ionizing exposure, calculated based on the data from all measurements in 2001-2020, is equal to 3,36 mSv/year. The study includes the analysis of the problems and perspectives of the improvement of the system of the data collection on the levels of exposure of the public of the Russian Federation from natural sources.